Changing conceptions of violence : the impact of domestic violence legislation in the Caribbean - Robinson, Tracy S. (1999)
Seeks to identify the major developments in the concept of violence found in the recent domestic violence legislation, the latter being examples of law, not only as 'practice and process' but also discourse, code and communication.